The Inefficiency of Zakat Management in BAZNAS Sragen Indonesia - Agus Wahyu Triatmo; Ravik Karsidi; Drajat Tri Kartono; Suwarto Suwarto (Afkaruna: Indonesian Interdisciplinary Journal of Islamic Studies, 2020)
The purpose of this paper is to analyze the problems of zakat governance in Indonesia, with the case study of BAZNAS in Sragen Regency. This is a qualitative research with the perspective of institutional theory. Results indicated that: (1) BAZNAS Sragen has a relatively high transaction cost due to several factors, particularly the costs of seeking information and monitoring; (2) BAZNAS Sragen conducts asymmetric information which is characterized by the lack of transparency, accountability, and fairness; (3) BAZNAS Sragen has a potential to perform opportunistic behavior in the form of political contamination in the distribution of ZIS funds. The less efficient of the governance causes the less optimal performance of BAZNAS Sragen, either in the limited amount of zakat fundraising or in its performance in empowering the poor.